Fungsi Sekuens Dixon Pada Pemeriksaan Mri Wrist Joint Dengan Kasus Dequervein Tenosinovitis Syndrome - I Ketut Narte Astape; Ni Putu Rita Jeniyanti; Nandra Nandra (Jurnal Anestesi, 2024)
Function Of Dixon Sequences In Wrist Joint Mri Examination In Dequervein Tenosynovitis Syndrome Cases. Magnetic Resonance Imaging (MRI) is the primary modality in patients with symptoms associated with De Quervain's Tenosynovitis Syndrome which is a stenosing tenosynovitis condition that affects the extensor tendons of the carpometacarpal and metacarpal joints of the thumb. The Dixon technique has the advantage of being able to produce fat images and water images. The basic principle of the Dixon technique is that each voxel has its signal coded periodically at a fixed offset. The purpose of using the Dixon sequence is to: analyze fluid and tissue which can differentiate between the firmness of fluid and tissue including nerves and blood vessels. The Dixon can press fat so that the boundaries are firm, the presence of muscle and fat infiltration can be seen. This research is a qualitative study using a case study method using 3 patients who underwent MRI Wrist Joint examinations in cases of Dequervein Tenosynovitis Syndrome. Data was collected using observation, documentation and interviews with radiographers and radiologists. The results of the data that have been collected can be concluded from the MRI Wrist Joint examination in cases of Dequervein Tenosynovitis Syndrome which was carried out at one of the hospitals in Jakarta, using the Sequence T1_tse_tra, T2_tse dixon_fs_cor, T2_tse_dixon_fs_sag, T1_vibe_we_cor, Pd_tse_fs_tra_2.5mm. Because by using the Dixon sequence the results obtained are more detailed in evaluating pathological abnormalities.